The use of purine analogues and infections (Hematology Meeting Reports, 2009)
In the 1980s, the purine analogues chemotherapy agents, fludarabine, deoxycoformycin, chlorodeoxyadenosine, were introduced into clinical usage for the care of patients with a variety of hematologic malignancies. These drugs have been mainly used in indolent lymphoproliferative neoplasms with effective hematologic responses, but they have been accompanied by a different spectrum of infections because of selective T-cell abnormalities which these agents determine.